2012
DOI: 10.3928/00989134-20120307-05
|View full text |Cite
|
Sign up to set email alerts
|

Use of Day Centers for Respite by Help-Seeking Caregivers of Individuals with Dementia

Abstract: Addressing the under utilisation of respite services in caregivers of people with dementia is an important task to improve social support amongst this vulnerable group. This paper utilises theory to conceptualise the behavioural, normative and control beliefs that caregivers of people with dementia associate with the use of out of home day centers for respite. Interviews and focus groups with 36 caregivers were undertaken to explore the beliefs of both users and non-users of services. Whilst service users held… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(84 citation statements)
references
References 27 publications
4
80
0
Order By: Relevance
“…Short and fixed opening hours and the lack of service during public holidays and vacations give relatives limited opportunities for an active social life, especially in the evenings. The need for flexible opening hours, as expressed by the family caregivers, confirms previous research that showed that flexible opening hours and programmes are important for the DCCs to provide respite [31,36,48]. Social stress is one of the factors affecting the burden on the family caregiver [10,12].…”
Section: Limited Opening Hours -Consequences For the Caregiver's Socisupporting
confidence: 79%
“…Short and fixed opening hours and the lack of service during public holidays and vacations give relatives limited opportunities for an active social life, especially in the evenings. The need for flexible opening hours, as expressed by the family caregivers, confirms previous research that showed that flexible opening hours and programmes are important for the DCCs to provide respite [31,36,48]. Social stress is one of the factors affecting the burden on the family caregiver [10,12].…”
Section: Limited Opening Hours -Consequences For the Caregiver's Socisupporting
confidence: 79%
“…Other methodological factors to consider (as recommended by previous reviews) include sample size (Neville & Byrne ), lack of explicit definitions of respite and respite type studied and unspecified participant inclusion/exclusion criteria (Flint , Lee & Cameron ). While some authors preferred to address different types of respite separately (Lee & Cameron , Phillipson & Jones ,b, ), others argued convincingly that a wider approach would serve better for understanding how respite services can meet individual carers' needs (Flint ).…”
Section: Resultsmentioning
confidence: 99%
“…, Madeo et al . , Phillipson & Jones , ). Activities that promote personal growth, lifelong learning and ongoing support and interaction with the carer appear to encourage more use of respite than programmes using other activities (Henry & Capitman ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, the existence of a tailored program based on specific knowledge of the person's needs and a feeling of shared responsibility with staff are described as examples of good quality (de Jong & Boersma, 2009;Phillipson & Jones, 2012). If we wish caregivers to support the use of day care, evidence about the quality of care therefore needs to be available and accessible.…”
Section: Day Care As a Respite Service For Caregiversmentioning
confidence: 99%